1997
DOI: 10.1021/bi970708z
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modification of Oat Phytochrome A:  Phosphorylation of a Specific Serine in a Multiple Serine Cluster

Abstract: Phytochrome A (phyA) is a photoreceptor of higher plants which mediates a variety of biochemical and physiological processes in response to red/far-red light. By detailed structural analysis of the peptides of the total tryptic digest of oat phyA, we found that the photoreceptor isolated from red light irradiated seedlings contains only one site of phosphate attachment, in the N-terminal Ser-rich region. The N-terminal tryptic phosphopeptide (residues 1-12) contains eight serine residues, any of which may be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…Ser598 phosphorylation occurs only in the Pfr form of phyA in red light-treated oat seedlings (McMichael and Lagarias, 1990;Lapko et al, 1999), whereas phosphorylation of other sites (Ser7 and Ser17) was found either Pr/Pfr indifferent or Pr specific (Lapko et al, 1996(Lapko et al, , 1997. In fact, the Ser598 phosphorylation was thought to play an active role in the phyA-mediated lightsignal transduction (Lapko et al, 1999;Park et al, 2000;Kim et al, 2002b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ser598 phosphorylation occurs only in the Pfr form of phyA in red light-treated oat seedlings (McMichael and Lagarias, 1990;Lapko et al, 1999), whereas phosphorylation of other sites (Ser7 and Ser17) was found either Pr/Pfr indifferent or Pr specific (Lapko et al, 1996(Lapko et al, , 1997. In fact, the Ser598 phosphorylation was thought to play an active role in the phyA-mediated lightsignal transduction (Lapko et al, 1999;Park et al, 2000;Kim et al, 2002b).…”
Section: Discussionmentioning
confidence: 97%
“…The sites of phytochrome phosphorylation in vivo and in vitro have been identified with oat (Avena sativa) phyA (McMichael and Lagarias, 1990;Lapko et al, 1996Lapko et al, , 1997Lapko et al, , 1999. There are two Ser sites, Serine-7 (Ser7) and , that are phosphorylated in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its protein level is rapidly reduced in response to light via transcriptional and posttranslational mechanisms (Canton and Quail, 1999;Clough et al, 1999;Seo et al, 2004). Furthermore, the phosphorylation state of phyA and therefore its activity and stability is light dependent (Lapko et al, 1997;Kim et al, 2004;Rubio and Deng, 2005;Trupkin et al, 2007). In addition, there is evidence that the phosphorylation state of the phyA dimer could lead to a preferential induction either of the FR-HIR or the VLFR pathway (Ryu et al, 2005;Trupkin et al, 2007;Kneissl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Like traditional kinases, phytochrome has been demonstrated to function as a phosphoprotein (McMichael and Lagarias, 1990;Lapko et al, 1997). The in vivo studies conducted on oat phyA showed phosphorylation at Serine-7 (irrespective of Pr/Pfr) and Serine-598 (Pfr specific) residues, whereas in vitro phosphorylation has been established at Serine-17 (Pr specific) and Serine-598 (Pfr specific) sites, respectively (Lapko et al, 1997(Lapko et al, , 1999.…”
Section: Phosphorylation and Kinase Activitymentioning
confidence: 99%